Analysis of the Implementation Process for Socioscientific Issues In the Context of the LearningExperience - Et, Sümeyra Zeynep; Gömleksiz, Mehmet Nuri (My University, 2021)
Purpose: This research was carried out to determine the experiences and views of candidate science teachers (CSTs) participating in the applications dealing with socioscientific issues. Design/Methodology/Approach: Phenomenological research design, a qualitative research method, was used in line with the purpose of the study. The study group consisted of third-year teacher candidates studying at the science department of a state university. Data were collected through student journals. Students who participated in the application were asked to write journals on a weekly basis. The goal was to evaluate the feelings and thoughts about socioscientific issues of the candidate teachers about the process through the journals. Data obtained from student journals were analyzed using the content analysis method. Findings: Some of the research results can be listed as follows: Candidate teachers stated that they did not participate in practices based on socioscientific issues before, and therefore, they stated that they had difficulties in subjects such as participating in discussions, conducting discussions, and making claims, especially in the first few weeks. With subsequent applications, they indicated that they were able to actively participate in the process. Further, it was determined that research on socioscientific issues and having discussions during the lesson was considered entertaining and interesting Highlights: Considering the results of this research, practices related to socioscientific issues can be used in situations where individuals want to participate actively in discussions and increase their motivation for discussions.
Keywords: Eğitim; Eğitim Araştırmaları